Pengembangan Media Pembelajaran Autoplay Media Studio Pada Mata Pelajaran Pendidikan Pancasila Dan Kewarganegaraan Terhadap Hasil Belajar Siswa Di Sman 5 Cilegon - Sohibudin Sohibudin; Desty Endrawati Subroto; Mohamad Bayi Tabrani (International Forum of Researchers and Lecturers, 2023)
This research is motivated to reduce the boredom experienced by students when participating in the teaching and learning process of Pancasila and citizenship education in class. Students no longer only sit, stay silent and listen to stories from the teacher, but students can interact directly with learning media based on Autoplay Media Studio 8 because in this learning media in addition to learning materials, there are also animations, images, videos, sounds and flash so that they can build new interests, arouse motivation and stimulate student learning activities.